HIGH-PRESSURE MELTING OF CARBONATED ECLOGITE AND EXPERIMENTAL CONSTRAINTS ON CARBON RECYCLING AND STORAGE IN THE MANTLE - Hammouda T. (My University, 2003)
High-pressure multi-anvil experiments (5 to 10 GPa) have been conducted on a basalt + calcite mixture in order to constrain the fate of carbonates carried on subducted ocean floor. Up to 6 GPa, carbonate breakdown occurs between 1100 and 1200°C, and is associated with silicate melting. At 6.5 GPa and above, carbonatitic melts are produced and the solidus temperature is located below 1000°C. Liquid immiscibility was found at 6 GPa and 1300°C. Compared with P -- T paths of subducting slabs, the present results suggest that carbonates will most likely be removed from the slab before reaching 300 km, and are unlikely to be introduced in the transition zone nor in the lower mantle by subduction. Therefore, the deep carbon cycle appears to be restricted to the upper mantle (300 km or shallower depth). Only anomalously carbonate enriched portions of the slab (fractures) could allow for oxidised carbon introduction to deeper mantle regions, but more experiments at higher pressure are necessary to evaluate this hypothesis. Compared with the peridotitic system, the carbonatitic solidus in eclogite is located about 4 GPa higher in pressure, and is located in the diamond stability field. This is due to the difference of silicate mineralogies involved in carbonation reactions. In addition, carbonatites produced in eclogite environment are calcium-rich (Ca / (Ca+Fe+Mg) ca. 0.80), in striking contrast to those produced by melting of carbonated peridotite (Ca / (Ca+Fe+Mg) ca. 0.50). Carbonated eclogite should therefore be considered as a potential source for calcic carbonated magmas in the upper mantle. The present experimental results also offer support to models involving genetic links between carbonated melts and diamond formation in the mantle.